Diagnostic Evaluation of Foreign Body Aspiration in Children - Ali Onur Erdem; Barlas Etensel; Mesut Yazıcı; Sezen Karaca Özkısacık (Journal of Pediatric Research)

(untitled)
Aim:The aim of this study was to evaluate the place of clinical symptoms and findings, and radiological imaging in the diagnosis of foreign body aspiration (FBA) in children, and to investigate the validity of existing diagnostic algorithms.Materials and Methods:The medical records of 120 children with a diagnosis of FBA who underwent rigid bronchoscopy were examined. The sensitivity and specificity of the parameters used in the diagnosis of FBA and their predictive values were calculated.Results:78.9% of the patients were younger than 3 years and 63.8% were male. The peak incidence was 18 months. The rate of negative bronchoscopy was 30.8% and 87.3% of these patients were younger than 3 years. It was observed that the value with the highest diagnostical sensitivity and diagnostic accuracy (DA) rate (sensitivity; 92.54% and DA; 85.7%) had positivity for any of the radiological findings, and among these, there was the detection of one-sided excessive ventilation on chest X-ray (sensitivity; 70.0% and DA; 70.01%). Patients with positivity of any of the radiological findings who additionally had wheezing together with cyanosis or dyspnea had 100% specificity.Conclusion:Particularly male children under the age of 3 years have an increased risk of FBA. Neither clinical symptoms nor radiological findings alone are sufficiently specific and sensitive in the diagnosis of FBA. The most important factor in the decision to perform bronchoscopy is the evaluation of radiological findings together with physical examination and history.